A CASE STUDY ON THE DIFFERENT RURAL EMPLOYMENT - ABSAR ALAM (International Journal of Multidisciplinary Research and Studies, 2020)
Some of these workfare schemes are structured as entitlements, with employment on public works projects being promised on demand. There is a significant body of research that investigates whether or not self-targeting is effective. Specifically, these address the question of whether or not participants of the programme come from among the poor, or whether or not the elite capture programme benefits instead – either as a result of the exercise of socio-political power, or as a result of multiple market failures that cause individuals who are less well-off to self-select out of participation in the programme. There is also study being done to determine whether or not these programmes (maybe by accident) turn away potential beneficiaries who are looking for aid. This practise is referred to as administrative rationing.